No significant effect of transcranial direct current stimulation (tDCS) found on simple motor reaction time comparing 15 different simulation protocols. (October 2016) - Horvath, Jared Cooney; Carter, Olivia; Forte, Jason D.
Abstract: Background: Research exploring the behavioral impact of transcranial direct current stimulation (tDCS) over M1 has produced homogenous results. The most common explanations to address this homogeneity concerns the differential impact of varied tDCS parameters (such as stimulation intensity or electrode montage). To explore this, we systematically examined the effects of 15 different tDCS protocols on a well-elucidated neurobehavioral system: simple visual motor reaction time (smRT). Methods: For the initial phase of this study, 150 healthy participants were randomly assigned to one of 5 experimental groups (2 mA anodal, 2 mA cathodal, 1 mA anodal, 1 mA cathodal, or sham) across 3 different conditions (orbitofrontal, bilateral, or extracephalic reference electrode location). The active electrode was always placed over M1 and tDCS lasted for 20 min. Starting 5 min prior to stimulation and running continuously for 30 min, participants were repeatedly presented with a visual cue centered on a computer monitor and asked to press a response button as quickly as possible at stimulus onset (stimuli number: 100 pre-, 400 during-, and 100-post stimulation - interstimulus interval: 1–3 s). Ex-gaussian distribution curves, miss, and error rates were determined for each normalized batch of 100 RTs and compared using a two-way ANOVA. As the largest group differences were seen with 2 mA anodal (compared to sham) stimulation using an orbitofrontal montage, an additional 60 healthy participants were recruited to further test for significance in this condition. Results: No significant impact of tDCS was seen on any parameter of smRT distribution, error rate, or miss rate, regardless of polarity, stimulation intensity, electrode montage, or stimulation-to-task relationship. Conclusion: Our results suggest that tDCS over M1 might not have a predictable or reliable effect on short duration smRT. Our results raise interesting questions regarding the mechanisms by which tDCS might modulate more complex motor behaviors. Additional research utilizing multiple tDCS protocols as undertaken here will help address and clarify these concerns. Highlights: Tested the effect of on & offline 1mA, 2mA, & Sham tDCS over M1 on RT using uni-, bi-lateral, & extracephalic montages. Regardless of the stimulation parameters utilized, tDCS had no effect on RT distribution, error, or miss rate. This large, systematic study strongly suggests tDCS over M1 does not impact any measure of motor reaction time.